The Place and Role of the Theory of State and Law in the System of the Humanities - Mavlonov Utkir Makhmasobirovich (Research Parks Publishers, 2021)
This article discusses the place and role of the theory of state and law in the system of humanities. In the article, the author analyzes the methodological connection of the theory of state and law with other disciplines